Lens Capsule Perforation Without Inflammation in 4 Rabbits From Intravitreal Injection Studies. (September 2017) - Farman, Cindy; Schuetz, Chris; Lorget, Florence; Bantseev, Vladimir; Calise, David; Thackaberry, Evan A.
Historically, it was thought that lens protein was sequestered, and injury to the lens capsule causing release of lens material into the eye would always result in ocular inflammation. Currently, it is believed that lens antigens are recognized as self, subject to normal T-cell tolerance. Three different single-dose intravitreal injection/implantation studies of 4 different test materials, ranging from 4 to 6 weeks in length, were performed in New Zealand White rabbits. The test materials included polymer microspheres, polymer rods, a solvent, and a hydrogel. Intravitreal injection/implantation procedures were performed on day 1, and indirect ophthalmoscopy and slit-lamp biomicroscopy examinations were performed by board-certified veterinary ophthalmologists periodically throughout the course of each study. None of the affected animals received corticosteroids or other immunomodulatory agents during the course of the studies. Four rabbits had perforation of the posterior lens capsule during the injection/implantation procedure on day 1, visible on clinical ophthalmic examination as lens capsule alterations described as "lens hits" and/or incipient posterior cataracts. Findings on slit-lamp biomicroscopy examination were limited to vitreous cells in 2 of the animals, although not centered on the area of lens capsule disturbance. Histologically, there was no evidence of inflammation in association with extruded lens protein material in any of the affected eyes. These results indicate that iatrogenic damage to the lens capsule during aseptically performed intravitreal injections/implantations does not appear to induce inflammation in rabbits.